An Error Analysis of The Inflectional Markings in EFL Students’ Academic Writing - Annisa Ainun Mardhiyah; Hastini; Desrin Lebagi; Darmawan (e-Journal of Linguistics, 2025)
This study aims to identify specific problems and provide insight into learners' difficulties in the inflectional markings learning and academic writing. The method of this research is Dulay’s Linguistics Category Taxonomy. The result of classification was calculated by the frequency of each error category: plural marks 13, present verb for third person singular 11, past verb 3, possessive noun 2, and past participle 1. Plural marks dominate the error of using the inflectional markings. The comparison and progressive marks are not found errors in EFL Students’ Academic Writing.